Normative Data for the NeuroCom® Sensory Organization Test in Subjects Aged 80–89 Years - Perucca, Laura; Robecchi Majnardi, Antonio; Frau, Silvia; Scarano, Stefano (Frontiers in Human Neuroscience, 2021)
Aging is known to increase the risk of falling. In older people, whose share in the total population is rising sharply, the sensory organization test (SOT, Equitest NeuroCom) is a useful tool during rehabilitation and in clinical research for assessing postural stability, risk of falling, and balance improvement. Normative data for the SOT in the healthy population older than 79 years have not been previously published. We recruited 53 recreationally active healthy subjects aged 80 years and older from the general population in a cross-sectional study. We presented the normative data for SOT for the 80–84 and 85-89 years groups. Our results showed that the “vestibular” balance control tended to be affected by aging more than the vision and proprioception-based systems. A striking reduction in performance after the age of 85 years was observed. These findings will be useful for clinical and research purposes.